'Cash and catamarans': 1980s British society through Howards' Way. Issue 3 (1st October 2019) - Fryers, Mark
This article explores the manner in which an extremely popular yet consequently (certainly critically) neglected television programme both represents the sociopolitical-economic culture that produced it and that is imbricated within these prevailing attitudes. Specifically, it explores the drama/soap Howards' Way (1985–90) and the manner in which its narrative logic and its aesthetic display and use of space, place and landscape is guided by the era's economic logic of excess, aspiration and hyper-monetization, and anxieties surrounding shifting gender roles. This article will explore the show's production history and the subsequent ethical ramifications as a show produced by a publically funded institution (the BBC). Drawing on specific textual analysis alongside critical reception and other contextualizing materials this article will demonstrate how popular television narrative makes meaningful the cultural context of its own production.